Thin or Thick Inclusiveness? The Constitutional Duty to Consult and Accommodate First Nations in Canada - Urquhart, I. (2019)
What has the addition of aboriginal rights to the Canadian constitution in 1982 meant for the place of First Nations’ interests in the Canadian constitutional order? This article considers this question in the context of natural resource exploitation – specifically, the exploitation of the oil or tar sands in Alberta. It details some of the leading jurisprudence surrounding Section 35 of the Constitution Act 1982, the section of the Constitution recognizing existing aboriginal and treaty rights. Arguably, Section 35 represented an important effort to improve the status of aboriginal peoples in Canada, to enhance the extent to which Canada included and respected the values and interests of First Nations. The article specifically considers how the judicial interpretation of the Crown’s duty to consult and accommodate aboriginal peoples is related to the theme of inclusivity. It argues that the general thrust of judicial interpretation has promoted a thin, or procedural, version of inclusiveness rather than a substantive, or thicker, one. Such a thicker version of inclusiveness would be one in which the pace of oil sands exploitation is moderated or halted in order to allow First Nations to engage in traditional activities connected intimately with aboriginal and treaty rights.